2021
DOI: 10.1590/1981-6723.07720
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of phenolic compounds from cowpea (Vigna unguiculata) by HPLC-DAD-MS/MS

Abstract: Vigna unguiculata (L.) Walp (cowpea), Fabaceae family and also known as Leguminosae, is an important vegetable used as food in tropical regions, especially in Africa, South America and Asia countries. Phenolic compounds are associated with important biological properties and their occurrence in edible plants may result in a highly functional food. Chromatographic profiles of phenolic compounds were investigated in two cowpea cultivars, such as tracuateua (CT) and caldeirão (CC), and both were cultivated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Another phenolic derivate is quercetin, considered an inhibitor of the development of different types of cancer, since this flavonoid can affect cell proliferation, cell cycle regulation and usually participate in multiple signaling pathways [26] [29] [30]. A third flavonoid identified in this study is kaempferol, that has also been reported to participate in biological properties such as anti-inflammatory, antioxidant and antimutagenic, reducing the risk of cancer and other diseases [25] [31] [32]. Cardozo et al (2011) quantified phenolic compounds in three species of red macroalgae, G. birdiae, G. domingensis and G. tenuistipitata, and reported that there was greater detection efficiency of the compounds in the use of methanol solvent, when compared to other solvents at different concentrations [33].…”
Section: Chemical Characterization Of Extracts Through Hplcmentioning
confidence: 99%
“…Another phenolic derivate is quercetin, considered an inhibitor of the development of different types of cancer, since this flavonoid can affect cell proliferation, cell cycle regulation and usually participate in multiple signaling pathways [26] [29] [30]. A third flavonoid identified in this study is kaempferol, that has also been reported to participate in biological properties such as anti-inflammatory, antioxidant and antimutagenic, reducing the risk of cancer and other diseases [25] [31] [32]. Cardozo et al (2011) quantified phenolic compounds in three species of red macroalgae, G. birdiae, G. domingensis and G. tenuistipitata, and reported that there was greater detection efficiency of the compounds in the use of methanol solvent, when compared to other solvents at different concentrations [33].…”
Section: Chemical Characterization Of Extracts Through Hplcmentioning
confidence: 99%
“…Studies indicate that cowpea seeds and leaves contain crude protein levels ranging from 22.0 to 30.0 % (4). Furthermore, as a vegetable, cowpea is abundant in vitamins, minerals and bioactive compounds like phenolic compounds, which are linked to various health benefits, including the prevention of diseases such as diabetes, cancer and cardiovascular conditions (5). Identified as a crop that can enhance food security and improve nutritional status, particularly in regions vulnerable to climate challenges, cowpea plays a crucial role in promoting human health and well-being (6).…”
Section: Introductionmentioning
confidence: 99%